1969
DOI: 10.1136/bmj.1.5644.599
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glucose Tolerance and Related Factors in a Normal Population Sample--II. Interrelationship of Glycerides, Cholesterol, and other Factors with the Glucose and Insulin Response

Abstract: Summary: The data available from the previous paper have been analysed to determine the interaction between the blood sugar and plasma insulin responses to oral glucose and a number of other biological variables.The total sugar and insulin responses were derived by calculating the total area and the incremental area under the curves.The blood sugar area was significantly correlated with age in both men and women, particularly the former. A striking degree of correlation was found in men between the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1971
1971
1999
1999

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Chiang et al (14) have reviewed 31 studies from all parts of the world that showed positive correlation between overweight and hypertension and 19 that showed reduction in blood pressure consequent upon weight reduction. Two excellent reports have similarly documented the relationship of obesity to diabetes with its attendant hypercholesterolemia (1,6).…”
Section: Health Consequences Of Obesity and Of Weight Reductionmentioning
confidence: 91%
“…Chiang et al (14) have reviewed 31 studies from all parts of the world that showed positive correlation between overweight and hypertension and 19 that showed reduction in blood pressure consequent upon weight reduction. Two excellent reports have similarly documented the relationship of obesity to diabetes with its attendant hypercholesterolemia (1,6).…”
Section: Health Consequences Of Obesity and Of Weight Reductionmentioning
confidence: 91%
“…This contention is supported by the highly significant association between internal cation imbalance and elevated triglycerides and urate. Elevated triglycerides are a prominent characteristic of hyperinsulinemia and insulin resistance, 25 ' x which are accompanied by overproduction of very low density lipoproteins. 26 An association of elevated triglycerides with altered cation transport mechanisms has recently been reported and hypothesized to reflect the effect of changes in plasma lipid levels on cellular membrane composition.…”
mentioning
confidence: 99%
“…The degree of control o~ hyperglycemia has been reported to influence serum lipids [3,4] and the majority of patients with elevated level of very low density lipoproteins (VLDL) in plasma exhibit abnormal glucose tolerance [5]. Little association, however, has been noted between the levels of plasma insulin and plasma cholesterol [6].…”
mentioning
confidence: 99%